2019
DOI: 10.2147/ndt.s211288
|View full text |Cite
|
Sign up to set email alerts
|

<p>Microglial activation and neurobiological alterations in experimental autoimmune prostatitis-induced depressive-like behavior in mice</p>

Abstract: Background Patients with chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) frequently show depressive symptoms clinically and increasing evidence indicates a correlation between CP/CPPS and depression. However, the underlying mechanisms of CP/CPPS-related depression remain poorly understood. Here, we sought to determine the role of hippocampal microglial activation and neurobiological changes in a mouse model of experimental autoimmune prostatitis (EAP)-induced depression and the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 41 publications
2
42
0
Order By: Relevance
“…The high risk of depression associated with CP/CPPS was confirmed in a clinical study and in EAP mice (6,31). The depressive state of animals is mainly manifested by a decrease in overall activity, reduced social communication activities, reduced exploratory activities, and defects in aggression and pleasure sensation (23,32).…”
Section: Discussionmentioning
confidence: 84%
“…The high risk of depression associated with CP/CPPS was confirmed in a clinical study and in EAP mice (6,31). The depressive state of animals is mainly manifested by a decrease in overall activity, reduced social communication activities, reduced exploratory activities, and defects in aggression and pleasure sensation (23,32).…”
Section: Discussionmentioning
confidence: 84%
“…In this study, we used EAP rats as subjects to explore the mechanism on the high incidence of PE in patients with prostatitis. Previous studies have shown that EAP rat is a mature animal model mimicking human CP/CPPS 8‐11,23 . However, no studies have been conducted to observe and evaluate the ejaculatory behavior of the EAP model.…”
Section: Discussionmentioning
confidence: 99%
“…These receptors and their neurotransmitters form complex networks of interactions, and our present results are probably an account of the balance of multiple effects. Currently, increasing researches have searched out various clues and regarded prostate‐derived inflammation cytokines as the key, who crossing the blood‐brain barrier to intervene the CNS 8‐11 . Therefore, developing practical clinical strategies, such as antibodies of inflammation cytokines, to eliminate or block prostate‐derived cytokines might cure or relieve PE symptom for CP/CPPS patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether gut microbiota involves in EAP‐induced depressive‐like behaviors in mice remains undetermined. Our previous work showed that emotional abnormity in EAP mice was related to microglial activation and subsequent neurobiological alterations in the brain 38 . Also, the gut microbiota has been reported to play a vital role in regulating microglial function via the gut‐brain axis 39 .…”
Section: Discussionmentioning
confidence: 99%